How do sheep exploit pastures? An overview of their grazing behaviour from homogeneous swards to complex grasslands - Dumont B.; Prache S.; Carrère P.; Boissy A. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
A better knowledge of the interactions between plants and herbivores is needed to define appropriate management strategies for animals and grasslands within the context of sustainable grazing systems. Small ruminants exploit a wide range of resources from homogeneous swards and grass-clover associations to highly biodiverse grasslands and shrubby rangelands. In this paper, we first analyse how sheep graze homogeneous swards or simple plant associations, which requires considering prehension and digestive constraints. In spatially heterogeneous environments, herbivores need to gather information about vegetation distribution and quality, and use that information to forage efficiently. We therefore then provide an overview of what we propose are some of the key cognitive and social processes that determine the use of vegetation mosaics by sheep. Finally, we identify the lack of knowledge in how herbivores exploit diverse and complex grasslands, and we consider discrimination and generalisation behaviours as well as animals' response to environmental uncertainties. The impact of sheep on the evolution of complex grasslands is illustrated by two medium-term surveys of sward biodiversity outcomes. We conclude on shrubland utilization by sheep and goats, and on research needs in order to extrapolate the knowledge from studies on grazing sheep to the management of shrublands by small ruminants.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)